ANALISIS STRATEGI PENGEMBANGAN BISNIS ALEN – ALEN MBAK SRIPIT MELALUI BUSINESS MODEL CANVAS - Putri, Sherly Yulia; Kusumaningtyas, Dian; Damayanti, Susi (Universitas Nusantara PGRI Kediri, 2023)
UMKMs in Trenggalek Regency are developing very rapidly. However, Alen-alen Mbak Sripit's business is still not widely known in the consumer market. So it hasn't developed much like other home industry businesses. This research aims to find out the analysis of the business strategy